(3GdNjd hUaGJgG hGfhGYgG hHjWQJgGs - (3Ydj Hf OGhO GdeDjO Hf jhSa GdeXaQ ; GdeLGgO GdQShdj,J (B764 (3g` s
(3ChdgG (B:s
(3fcJ eSJfSNI bGdgG LGeYgG(B: (3hLOJ JYGdjb HNW GdSdWGf Gdedc GdeLGgO CYfi GdOhGH cGaI hGNjd NGUI, hbO YdefG CehQge heG jaYdhf ef NOeJge s
(3BNQgG (B:s
(3hGcKQ eGjYjT Gdajd YfOfG ai Gdjef NeShf Ch SJhf SfI heG OhfgG hGddg SHMGfg hJYGdi CYde s
(3GfXQ fSNI CNQi HQbe (B49 (3afhf MQHjI haQhSjI HGSe (B: (3fcJ eSJfSNI h (B52 (3WH HGSe GdJPcQI aj eYQaI GdHjWQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B90s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI Sja GdESdGe YHOGddg HUfYGA s
Keywords: (3GdWHs